Lamb mode diversity imaging for non-destructive testing of plate-like structures - Prado, Vander T. [UNESP]; Higuti, Ricardo T. [UNESP]; Kitano, Cláudio [UNESP]; Martínez-Graullera, Óscar; Adamowski, Julio C. (Elsevier, 2013)
Several Lamb wave modes can be coupled to a particular structure, depending on its geometry and transducer used to generate the guided waves. Each Lamb mode interacts in a particular form with different types of defects, like notches, delamination, surface defects, resulting in different information which can be used to improve damage detection and characterization. An image compounding technique that uses the information obtained from different propagation modes of Lamb waves for non-destructive testing of plate-like structures is proposed. A linear array consisting of 16 piezoelectric elements is attached to a 1 mm thickness aluminum plate, coupling the fundamental A0 and S0 modes at the frequencies of 100 kHz and 360 kHz, respectively. For each mode two images are obtained from amplitude and phase information: one image using the Total Focusing Method (TFM) and one phase image obtained from the Sign Coherence Factor (SCF). Each TFM image is multiplied by the SCF image of the respective mode to improve contrast and reduce side and grating lobes effects. The high dispersive characteristic of the A0 mode is compensated for adequate defect detection. The information in the SCF images is used to select one of the TFM mode images, at each pixel, to obtain the compounded image. As a result, dead zone is reduced, resolution and contrast are improved, enhancing damage detection when compared to the use of only one mode. © 2013 Elsevier Ltd.
Keywords: Arrays; Damage detection; Image compounding; Lamb wave modes; Compounding techniques; Dispersive characteristic; Lamb wave mode; Non destructive testing; Piezoelectric elements; Plate-like structure; Sign coherence factors; Nondestructive examination; Surface defects; Ultrasonic waves; Plates (structural components)